Nesting ecology and nest survival of lesser prairie‐chickens on the Southern High Plains of Texas. Issue 5 (13th May 2014) - Grisham, Blake A.; Borsdorf, Philip K.; Boal, Clint W.; Boydston, Kathy K.
ABSTRACT The decline in population and range of lesser prairie‐chickens (Tympanuchus pallidicinctus) throughout the central and southern Great Plains has raised concerns considering their candidate status under the United States Endangered Species Act. Baseline ecological data for lesser prairie‐chickens are limited, especially for the shinnery oak‐grassland communities of Texas. This information is imperative because lesser prairie‐chickens in shinnery oak grasslands occur at the extreme southwestern edge of their distribution. This geographic region is characterized by hot, arid climates, less fragmentation, and less anthropogenic development than within the remaining core distribution of the species. Thus, large expanses of open rangeland with less anthropogenic development and a climate that is classified as extreme for ground nesting birds may subsequently influence nest ecology, nest survival, and nest site selection differently compared to the rest of the distribution of the species. We investigated the nesting ecology of 50 radio‐tagged lesser prairie‐chicken hens from 2008 to 2011 in the shinnery oak‐grassland communities in west Texas and found a substantial amount of inter‐annual variation in incubation start date and percent of females incubating nests. Prairie‐chickens were less likely to nest near unimproved roads and utility poles and in areas with more bare ground and litter. In contrast, hens selected areas dominated by grasses and shrubs and close to stock tanks to nest. Candidate models including visual obstruction best explained daily nest survival; a 5% increase in visual obstruction improved nest survival probability by 10%. The model‐averaged probability of a nest surviving the incubation period was 0.43 (SE = 0.006; 95% CI: 0.23, 0.56). Our findings indicate that lesser prairie‐chicken reproduction during our study period was dynamic and was correlated with seasonal weather patterns that ultimately promoted greater grass growth earlier in the nesting season that provided visual obstruction from predators. © 2014 The Wildlife Society.